Integration of bending operation in hybrid additive manufacturing chains based on powder bed fusion - Cristino Valentino; Sampaio Rui; Pragana João; Bragança Ivo; Silva Carlos; Martins Paulo (MATEC Web of Conferences)
The concept of integration of conventional manufacturing technologies with metal additive manufacturing, namely metal forming, has gained interest within the research community and the industry due to its potential to overcome the limitations of long build times and reduced build volumes of laser powder fusion, expanding their applicability by making use of the advantages of each approach. This study focuses on the optimization of the production sequence of additively manufactured slender three-dimensional custom parts with specific angles by hybridization of metal additive manufacturing with bending. The methodology is based on experimental data obtained from the mechanical and formability characterization of the material through uniaxial tension and three-point bending tests, conducted in both its as-built and heat-treated conditions. This is complemented by finite element analysis of bending stages applied to a slender, three-dimensional, double U-shaped part. The study compares and analyses its fabrication using conventional laser powder bed fusion and hybrid additive manufacturing with bending. Results indicated that the understanding of the formability limits of the material and the use of finite element analysis in the part design for hybrid additive manufacturing can improve significantly the overall effectiveness of the process in terms of material saving, fabrication time and geometric tolerances.